Comparative evaluation of the efficacy of intravenous paracetamol and ibuprofen on the treatment of tonsillopharyngitis with fever: A prospective, randomized controlled, double-blind clinical trial - Gizem Oncel (Wolters Kluwer Medknow Publications, 2021)
OBJECTIVE: Tonsillopharyngitis is one of the constituents of upper respiratory tract infection (URTI). Fever is a URTI symptom requiring treatment due to the occurrence of discomfort and high fever-based complications. This study primarily sets out to observe and compare the efficacy of intravenous administration of paracetamol and ibuprofen drugs on fever in adult patients with tonsillopharyngitis.METHODS: This study was performed in a prospective, randomized controlled, double-blind design. The study population was divided as Group 1 (treated with paracetamol) and as Group 2 (treated with ibuprofen). While the first group was treated with paracetamol as 1000 mg in 150 ml normal saline, the second group was treated with ibuprofen as 400 mg in 150 ml normal saline. The primary outcome was the decrease in fever at 15, 30, and 60 min, while the secondary outcome was the need for additional treatment after 60 min.RESULTS: One hundred and eighty-five patients were included in the final analysis. The mean age of the paracetamol group (57.4% male) was 28.36 ± 9.6, whereas that of the ibuprofen group (54.9% male) was 27.45 ± 7.98. Fever was reduced significantly between 0 and 60 min in both groups (P ≤ 0.001 and P ≤ 0.001, respectively). Although the antipyretic effect of ibuprofen was more pronounced in the early period than that of paracetamol, no significant difference was noted between the two groups in terms of fever drop between 0 and 60 min (P = 0.350).CONCLUSION: Although both drugs prove effective in controlling fever at the 60 min, stronger efficacy of ibuprofen in the first 15 min may enable rapid discharge from the emergency department.